Improving bank profits : the cost control approach to increasing income - Jannott, Paul F. (Chicago, Ill. : Bankers Pub. Co. : Probus Pub. Co., 1993)
Tells how to reduce personnel costs, increase fee income, control equipment costs, and minimize operation losses due to error
Includes index.
rua 09/11/2016
Loans
Keywords: Banks and banking; Bank management; Banks and banking--Cost control